Pengurusan Konflik dan Ciri Kepimpinan Pelajar Berdasarkan Jantina : Satu Kajian di SMK Syed Ahmad, Tambun Tulang, Arau, Perlis - Amir Faisal, Akbar (2010)
The purpose of this research is to study is to investigate the relationship between leadership and styles of managing conflict based on gender among students in SMK Syed Ahmad, Tambun Tulang, Arau, Perlis. Thus, either the significant exist between gender and styles of managing conflict or leadership were carry out in this research. 140 form two and form four students from SMK Syed Ahmad, Tambun Tulang, Arau, Perlis served as the unit of analysis for the data generated. The items for leadership traits are built based on the cluster of autocratic, democratic and laissez faire as introduced by leadership scholars and was modified into leadership based on task (task oriented), based on relationship (relationship oriented) and passive. As for styles of managing conflict, Kilmann-Thomas Model (1974,1977,1978) was based upon. The hypothesis were then tested using t-test and Pearson Correlation Test. All hypothesis were test for significant level of p=0.05. From the test done, it is stated that there is no significant between gender with leadership and style of managing conflict. A significant finding is detected between leadership based on relationship oriented with styles of managing conflict of collaboration and competition. Thereby, the finding implied towards secondary school administration and to whom it may concern. The connotation of this study is that students should be upgraded with leadership and styles of managing conflict especially those who live in the rural area.